A convenção das Nações Unidas contra a corrupção e seus reflexos nos programas de compliance nas empresas brasileiras - Schlichting, Fabio (2024)
This work analyzes the impacts of the United Nations Convention against Corruption through compliance programs in the Brazilian business environment, which is currently developing mechanisms to combat corruption. The aim is to broaden the perception of compliance experts, identifying in the national legal framework another tool to combat this significant social problem. Compliance programs in Brazil, driven by the Anti- Corruption Act for a decade, have yielded positive results, bringing Brazilian society closer to the ideal of a nation that does not condone unlawful practices within corporate activities. This work is relevant as it brings greater visibility to the subject and aims to stimulate deeper discussions. Scientifically researching the social phenomenon of corruption in the business world involves identifying opportunities for improving the state itself through integrity programs within companies. The research is a literature review that focuses on the impacts of the United Nations Convention against Corruption, its history, state accountability, corporate (public and private) accountability, and individual accountability in a global context.